Clinical Manifestations, Laboratory Findings and Complications of Pediatric Scrub Typhus in Eastern Taiwan - Wai-Tim Jim; Nan-Chang Chiu; Wai-Tao Chan; Che-Sheng Ho; Jui-Hsing Chang; Shi-Yu Huang; Sun Wu (Elsevier, 2009)
Scrub typhus is a clinically important endemic disease in Taiwan. The aims of this study were to analyze the clinical manifestations, laboratory data and complications of pediatric scrub typhus in eastern Taiwan. Patients and Methods: We searched medical records for all patients with scrub typhus who were hospitalized between 1992 and 2002 at the Taitung branch of Mackay Memorial Hospital, Taiwan. Records of children under the age of 18 with a confirmed diagnosis were selected for retrospective review. Results: During the study period, 145 patients fulfilled the diagnostic criteria for scrub typhus, of whom 106 (73%) were adults and 39 (27%) were children. The mean age of the children was 7.6 ± 4.6 years. The most common clinical manifestations of pediatric scrub typhus were fever (n = 39; 100%), cough (n = 28; 72%), anorexia (72%), eschar (69%), chill (67%) and lymphadenopathy (64%). The most common complications were hepatic dysfunction (77%) and pneumonitis (54%). Three children (8%) required intensive care, but the overall survival rate was 97%. One child died with multi-organ failure within 8 hours after admission. Conclusion: Scrub typhus should be considered in children with fever and hepatic dysfunction, particularly in those with a history of environmental exposure in an endemic area for scrub typhus. The presence of an eschar offers an important diagnostic clue, but not for all cases. Children with scrub typhus may develop serious complications and may even die if appropriate treatment is not given. Doxycycline is an effective antibiotic for pediatric scrub typhus in Taiwan.